Social Health Insurance and Labor Market Outcomes : Evidence from Central and Eastern Europe, and Central Asia - Wagstaff, A.; Moreno-Serra, R. (2012)
OBJECTIVE: The implications of social health insurance (SHI) for labor markets have featured prominently in recent debates over the merits of SHI and general revenue financing. It has been argued that by raising the nonwage component of labor costs, SHI reduces firms' demand for labor, lowers employment levels and net wages, and encourages self-employment and informal working arrangements. At the national level, SHI has been claimed to reduce a country's competitiveness in international markets and to discourage foreign direct investment (FDI). The transition from general revenue finance to SHI that occurred during the 1990s in many of the central and eastern European and central Asian countries provides a unique opportunity to investigate empirically these claims. METHODOLOGY/APPROACH: We employ regression-based generalizations of difference-in-differences (DID) and instrumental variables (IV) on country-level panel data from 28 countries for the period 1990-2004. FINDINGS: We find that, controlling for gross domestic product (GDP) per capita, SHI increases (gross) wages by 20%, reduces employment (as a share of the population) by 10%, and increases self-employment by 17%. However, we find no significant effects of SHI on unemployment (registered or self-reported), agricultural employment, a widely used measure of the size of the informal economy, or FDI. IMPLICATIONS FOR POLICY: We do not claim that our results imply that SHI adoption everywhere must necessarily reduce employment and increase self-employment. Nonetheless, our results ought to serve as a warning to those contemplating shifting the financing of health care from general revenues to a SHI system.